THE RELEVANCE THE «ETHNOGRAPHIC FACT» CATEGORY: PART 2. THE FACT AND INFORMATION - V. . Dmitriev (Гуманитарные и юридические исследования)
In the present article an ethnographic fact is viewed as information about an ethnic group and its culture. The content of an ethnographic fact is archaic - preserved relicts. The peculiarities of the source are determined not only by its properties as a medium of information, but also branches of science: descriptive ethnography, theoretical ethnography and ethnographic museum science.